THE ROLES OF PEOPLE IN ACTION FOR PROTECTING ONE’S RIGHTS AND OTHERS FROM CRIME IN SOCIETY - kayanha, Aroon (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2021)
This academic article is part of research on “Leadership, Organizational Support, and Police Officer Performance in Subunits of Stations of the Metropolitan Police Division” which has identified various crime problems and a steady increase. While the police station, which is an agency involved in the prevention and suppression of crime, has some limitations, such as area of responsibility and number of police officers, etc. In order to reduce these restrictions and increase guidelines for improving the performance of police officers, we should pay attention to the roles of the people in crime prevention and suppression. Therefore, the purpose of this article is to study the roles and capabilities of people under the laws in action for protecting their rights and others from crimes. The analysis found that the roles and capabilities of people under the laws in action for protecting one’s rights and others from crimes can be classified into two forms: (1) voluntary action form, it is a voluntary action of the people without hope of recompense and (2) compulsion by law form, such as to be a witness and assist the police officers to arrest the offender when requested by the officers.